Influence of Work Environment, Education, and Compensation on Employee Performance of PT. Sumo Internusa Indonesia - Deni Faisal Mirza; Winsen Ewin Dado Pasaribu; Ells Kissy Pangaribuan; Rivaldy (Kusuma Negara Business School, 2021)
The purpose of this study was to examine how the influence of the work environment, education and compensation on the performance of employees of PT. Sumo Internusa Indonesia. The decline in the level of employee performance is due to the work environment, education and compensation that are not appropriate. The population and sample in this study amounted to 62 employees. The research method uses multiple linear regression analysis techniques. The results of partial hypothesis testing obtained tstatistic > ttable or 2,157 > 2,001 and significant obtained 0,015 < 0,05, tstatistic > ttable or 3,163 > 2,001 and significant obtained 0,001 < 0,05, tstatistic > ttable or 4,852 > 2,001 and significant obtained 0.000 <0.05. The calculated F value (21.712) > F table (2.76) and the significance probability is 0.000 < 0.05. The conclusion in this study shows that partially the work environment, education and compensation have a positive and significant effect on employee performance. and simultaneously the work environment, education and compensation have a positive and significant effect on employee performance at PT. Sumo Internusa Indonesia.